2021
DOI: 10.3389/fendo.2021.638608
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surgical Complications Rates Between LigaSure Small Jaw and Clamp-and-Tie Hemostatic Technique in 1,000 Neuro-Monitored Thyroidectomies

Abstract: Over the past decade, the use of neuromonitoring in thyroid surgery has become well established and is increasing accepted across the world. In addition, new developments in energy devices have significantly improved efficacy in achieving hemostasis in thyroid surgery. Few studies focused on the complication rates in energy device-assisted sutureless neuro-monitored thyroidectomy. This study investigates a novel LigaSure Small Jaw (LSJ) technique for sutureless thyroidectomy and compares the surgical complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 31 publications
(27 reference statements)
0
19
0
2
Order By: Relevance
“…3) All patients with thermal RLN injury in this study had unrecovered VFM (U Group). RLN thermal injury is difficult to be detected visually and the risk of permanent palsy is high, surgeons should maintain vigilance in modern thyroid surgery that increases the use of energy-based devices ( 24 ). Compared to relatively mild mechanical injuries, thermal injuries sustained during surgery may require earlier voice intervention ( 25 ) performed under comprehensive postoperative laryngofiberscopy and voice analysis.…”
Section: Discussionmentioning
confidence: 99%
“…3) All patients with thermal RLN injury in this study had unrecovered VFM (U Group). RLN thermal injury is difficult to be detected visually and the risk of permanent palsy is high, surgeons should maintain vigilance in modern thyroid surgery that increases the use of energy-based devices ( 24 ). Compared to relatively mild mechanical injuries, thermal injuries sustained during surgery may require earlier voice intervention ( 25 ) performed under comprehensive postoperative laryngofiberscopy and voice analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the nerve injury mechanisms are significantly differed between the two groups. No patients in the clamp-and-tie group had thermal injury, whereas one-third of patients in the EBD group suffered thermal injury caused by lateral thermal spread in palsied RLNs (6).…”
Section: Introductionmentioning
confidence: 87%
“…Most intraoperative thermal injuries to the RLN result from thermal spread during use of high-temperature electrocautery devices and EBDs. Tissue contraction during EBD activation increases the risk of thermal injury because it reduces the distance from the RLN at which an EBD can be safely used (6). Thermal injury to the RLN often occurs unexpectedly when an EBD is activated or used for dissection.…”
Section: Intraoperative Neuromonitoring and Rln Thermal Injury Caused By Ebdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraoperative neural monitoring (IONM) is now an integral aspect of thyroid surgery in many centers. Interest in IONM, the number of institutions that perform, and societies that recommended monitored thyroidectomies have increased throughout the world in recent years (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). A recent international survey (16) of over 1,000 surgeons revealed that IONM is highly prevalent with 83% of surgeons using IONM in some or all of their cases.…”
Section: Introductionmentioning
confidence: 99%